RESPON TANAMAN PADI GOGO (Oryza sativa L.) TERHADAP STRESS AIR DAN INOKULASI MIKORISA - Harmastini Sukiman; Adiwirman Adiwirman; Syofiatin Syamsiyah (BERITA BIOLOGI, 2010)
It has been known that upland rice production is lower than low land rice production because it is inhibited by soil fertility, water supply and pest.One solutions to increase the production of upland rice is by applying the potential soil microorganism known as mycorrhizae.The objective of this research is to know thef Vesicular Arbuscular Mycorrhizae (VAM) role for upland rice under water stress condition. The research was conducted in greenhouse of Cikabayan, Bogor Agricultural University and Soil Microbiology Laboratory of Research Centre of Biotechnology, Indonesian Institute of Science Centre. The experimental design was factorial randomized block design with two factors. The first factor is inoculation of mycorrhizae consisted of two treatment i.e. without mycorrhizae (MO) and with mycorrhizae (Ml); while the second factor is water stress regime consisted of five treatments namely well watered (SO), water stress on tillering stage (SI), primordial stage (S2), anthesis stage(S3) and grain filling stage(S4). Mycorrhizae significantly increased root infection, phosphate uptake, height, number of tillering, leaf, Leaf Area Index (LAI), productive tillering, filled grain, grain weight and yield. While, water stress significantly decreased number of root infection, shoot wet fresh weight, root dry weight, increased phosphate uptake and sterilized grain, but it didn't significantly decrease yield. The interaction both mycorrhizae and water stress didn't significantly influence all variables, except the root dry weight. The inoculation of mycorrhizae could increase 19.62% on SI, 17.32% on S2, 29.14% on S3, 6.89% on S4 dried harvested yield.